Dual-Color and High-Energy X-Ray Kirkpatrick–Baez Microscope for Laser Plasma Research - Mingtao Li; Jiapeng Shi; Mingxun Wang; Jie Xu; Xin Wang; Baozhong Mu; Jianjun Dong; Kuan Ren; Wei Liu; Xing Zhang; Dong Yang (Photonics, 2025)
High-energy X-ray diagnostic systems are crucial for understanding hotspot high-density area asymmetry, fuel mixing, and other phenomena in inertial confinement fusion. To meet the demand for hotspot electron temperature measurements, we developed a high-energy dual-channel Kirkpatrick–Baez microscope. This microscope is characterized by a dual high-energy response and high spatial resolution, enabling the observation of fine structures in high-density regions of a hotspot. Spectral drift was effectively mitigated by optimizing the grazing incidence angle, and the spatial and spectral domains were coupled through experimental alignment. Herein, we describe the optical design of the proposed microscope. Furthermore, we performed simulations and backlight imaging to validate the performance of the proposed system. The results show that the spatial resolution was better than 3 μm in the center and better than 6.5 μm in a field of view of 300 μm. The spectral response efficiencies at 11.4 and 17.48 keV were 7.41 × 10−8 and 5.77 × 10−8 sr, which deviate from the theoretical values by 3.01% and 6.79%, respectively.